Diffusion tensor imaging assessments to investigate motor impairment recovery after minor basal ganglia hemorrhage post-stereotactic surgery - Liao, Changpin; Lu, Zhen; Pan, Guiying; Ye, Jing; Nong, Shengde; Nordin, Rusli; Liang, Jiancheng; Fazel, Muhammad Fattah; Baharin, Nurul Hana Zainal (Frontiers in Neuroscience, 2025)
ObjectiveTo investigate the efficacy of diffusion tensor imaging (DTI) in assessing the motor impairment resulting from minor basal ganglia hemorrhage post-stereotactic surgery.MethodsA total of 104 patients with minor basal ganglia hemorrhages (hematoma volume ≤15 ml) underwent DTI within 48 h and 1 month post-treatment. Patients were divided into two groups: 42 in the experimental group, receiving stereotactic surgery and medication, and 62 in the control group, receiving medication alone. The corticospinal tract (CST) of the posterior limb of the internal capsule was the region of interest (ROI) for assessing mean FA values on both sides. Fugl-Meyer motor function (FMF) scores were recorded within 48 h and 1 month post-treatment, and Modified Rankin Scale (MRS) scores at 6 months.ResultsAfter 1 month of treatment, the FA values and FMF scores for the affected side of patients in the experimental group were 0.34 ± 0.17 and 67.84 ± 4.72, respectively, significantly surpassing those of the control group, which were 0.21 ± 0.06 and 45.38 ± 2.25 (P < 0.05). After 6 months of treatment, the experimental group exhibited MRS scores of 10 cases (23.81%) at grade 0, 12 cases (28.57%) at grade 1, 16 cases (38.10%) at grade 2, 2 cases (4.76%) at grade 3, 2 cases (4.76%) at grade 4, and 0 cases at grade 5. In contrast, the control group demonstrated 8 cases (12.90%) at grade 0, 12 cases (19.35%) at grade 1, 18 cases (29.03%) at grade 2, 15 cases (24.19%) at grade 3, 6 cases (9.68%) at grade 4, and 3 cases (4.84%) at grade 5. There are 18 cases (29.03%) in grade 2, 15 cases (24.19%) in grade 3, 6 cases (9.68%) in grade 4, and 3 cases (4.84%) in grade 5 within the control group. The experimental group showed a significantly better MRS score compared to the control group (P < 0.05).ConclusionDTI can accurately evaluate the structural integrity of the CST in patients with minor basal ganglia hemorrhages following stereotactic surgery, particularly regarding the CST pathways involved in motor control, providing valuable guidance for clinical treatment.